Literature review: Analysis of the influence of competence, motivation, and organizational commitment on employee performance through employee engagement - Erni Pratiwi Perwitasari; Cecep Pahrudin; Rr Endang Wahyuni; Esterlinus Edwin Lermatan; Sugiyanto Sugiyanto (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to develop hypotheses related to factors that influence employee engagement and performance, especially in cargo companies. Research Methodology: The approach used in this literature review is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this study and is sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage Q2-Q4, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar, and digital reference books. Results: The findings of this literature review indicate that competence, motivation, and organizational commitment each have a direct impact on employee engagement in cargo companies. These three variables also directly influence employee performance. In addition, employee engagement itself plays a significant role in shaping employee performance. Furthermore, competence, motivation, and organizational commitment are also found to influence employee performance indirectly through the mediating role of employee engagement within cargo companies. Conclusions: Competence, motivation, and commitment enhance employee engagement and performance in cargo companies. Limitations: This study examines competence, motivation, and commitment influencing engagement performance. Contribution: This study examines competence, motivation, and commitment affecting performance.